287 Safety and antitumor activity of indoleamine 2, 3-dioxygenase 1 (IDO-1) inhibitor KHK2455 in combination with anti-CCR4 monoclonal antibody mogamulizumab in patients with advanced solid tumors. (9th November 2020) - Sahebjam, Solmaz; Muzaffar, Jameel; Yap, Timothy; Hong, David; Rixe, Olivier; Brown-Glaberman, Ursa; Varga, Andreea; Massard, Christophe; Baldini, Capucine; Efuni, Sergey; Kapelan, Barbara; Liu, Yi; et al.
Abstract : Background: IDO-1 inhibitors have shown antitumor activity in combination with immunotherapeutic agents in multiple cancers. KHK2455 is a novel and selective oral IDO-1 inhibitor. KHK2455 inhibits IDO-1 apo-enzyme, with long-lasting and potent activity. Mogamulizumab is an anti-C-C chemokine receptor 4 (CCR4) monoclonal antibody that has shown synergy with KHK2455 in preclinical models. Mogamulizumab is approved in the US and EU for treatment of mycosis fungoides and Sézary syndrome. Methods: In this first-in-human study, patients with advanced solid tumors received escalating oral doses of KHK2455 alone (0.3, 1, 3, 10, 30 and 100 mg once daily) for 4 weeks (Cycle 0), followed by combination with 1 mg/kg weekly of IV mogamulizumab for 4 weeks (Cycle 1), and then on Days 1 and 15 (from Cycle 2 onward) in a standard 3+3 Phase I design. Safety, tolerability, pharmacokinetics and IDO activity (kynurenine [Kyn] and tryptophan [Trp] levels and ex vivo Kyn production) were evaluated. Results: Thirty-six patients were enrolled across all cohorts. One patient with lower esophageal cancer in the 100 mg cohort exhibited dose-limiting toxicity (Grade 3 gastrointestinal necrosis). The most frequent (≥10%) treatment-emergent adverse events (TEAEs) are presented in table 1. Overall numbers of TEAEs, ≥Grade 3 TEAEs, and serious TEAEs related to KHK2455 and mogamulizumab are presented in table 2. Serious KHK2455-related TEAEs included gastrointestinal necrosis (KHK2455 monotherapy), and nausea and drug eruption (combination therapy). In addition, five drug-related TEAEs in combination therapy led to discontinuation; there were no fatal outcomes related to either study drug. Plasma KHK2455 concentrations reached steady state by Day 8 (Cycle 0) and increased dose-dependently. Potent dose-dependent inhibition of IDO activity was demonstrated by plasma Kyn concentration and Kyn/Trp ratio (median inhibition 70.5% and 70.8%, respectively, at 100 mg dose on Day 15, compared to baseline) and ex vivo Kyn production (>95% inhibition at ≥10 mg KHK2455), confirming target modulation. Six of 26 evaluable patients from all dosing groups achieved durable disease stabilization (≥6 months, RECIST 1.1), and one patient with bevacizumab-resistant glioblastoma demonstrated confirmed partial response (43.5% tumor reduction over a 2-year observation period). Median overall survival was 13.4 months, with 30% of subjects surviving for 2 years or longer (figure 1). Conclusions: KHK2455 in combination with mogamulizumab was well-tolerated and manageable at all doses tested, suppressed Kyn production in a dose-dependent and sustained manner, and demonstrated signals of antitumor activity. These data support the continued development of this combination. Acknowledgements: Medical writing assistance was provided by Susan E. Johnson, PhD, S.E. Johnson Consulting, LLC, New Hope, PA, USA. Trial Registration: NCT02867007 (www.clinicaltrials.gov) Ethics Approval: This study was approved by Ethics Committees at all participating study institutions.